2023
DOI: 10.1093/ofid/ofad017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Early Syphilis Among Men Who Have Sex With Men in Australia, 2013–2019: A Retrospective Cohort Study

Abstract: Background We aimed to examine the incidence of syphilis in men who have sex with men (MSM) and identify subgroups of MSM at a higher risk of syphilis infection. Methods We conducted a retrospective cohort study of MSM attending a sexual health clinic in Australia during 2013–2019, who had at least two syphilis serological tests during the study period. The incidence of syphilis was expressed as per 100 person-years. A cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
4
3
0
Order By: Relevance
“…The overall incidence rate of syphilis in our men living with HIV was 6.0/100 PYFU and the annual incidence rate ranged from 3.3/100 PYFU in 2018 to 9.3/100 PYFU in 2021. Similarly, to our findings in 2021, a retrospective cohort study from Australia reported an incidence of early syphilis of 9.3 per 100 person-years in MSM living with HIV in the period 2013–2019 22 . Another study from Thailand found an incidence of syphilis of 10.2 per 100 person-years in a predominantly MSM cohort diagnosed with acute HIV infection in the period April 2009 through December 2018 23 .…”
Section: Discussionsupporting
confidence: 91%
“…The overall incidence rate of syphilis in our men living with HIV was 6.0/100 PYFU and the annual incidence rate ranged from 3.3/100 PYFU in 2018 to 9.3/100 PYFU in 2021. Similarly, to our findings in 2021, a retrospective cohort study from Australia reported an incidence of early syphilis of 9.3 per 100 person-years in MSM living with HIV in the period 2013–2019 22 . Another study from Thailand found an incidence of syphilis of 10.2 per 100 person-years in a predominantly MSM cohort diagnosed with acute HIV infection in the period April 2009 through December 2018 23 .…”
Section: Discussionsupporting
confidence: 91%
“…The overall incidence rate of syphilis in our men living with HIV was 6.0/100 PYFU and the annual incidence rate ranged from 3.3/100 PYFU in 2018 to 9.3/100 PYFU in 2021. Similarly, to our ndings in 2021, a retrospective cohort study from Australia reported an incidence of early syphilis of 9.3 per 100 person-years in MSM living with HIV in the period 2013-2019 [22]. Another study from Thailand found an incidence of syphilis of 10.2 per 100 person-years in a predominantly MSM cohort diagnosed with acute HIV infection in the period April 2009 through December 2018 [23].…”
Section: Discussionsupporting
confidence: 76%
“…Risk factors associated with syphilis such as being MSM and having a history of previous syphilis have also been reported previously [22,23,27,[40][41][42][43]. Younger age was also associated with syphilis; however, this relationship was not as strong as in other studies [40,43].…”
Section: Discussionsupporting
confidence: 74%
“…For instance, multivariate analysis estimated that GBMSM with concurrent gonococcal or chlamydial infection had a 60% higher risk of syphilis compared with GBMSM without gonococcal or chlamydial infection. 25 Given the likelihood that gonococcal infections are frequently exposed to doxy-PEP, this potentially undermines gonococcal antimicrobial stewardship efforts by accelerating the spread of gonococcal AMR 26 and potentially selecting for multidrug-resistant gonococcal strains. 27 By averting gonorrhoea infection, the doxy-PEP study reduced ceftriaxone use by half in the doxy-PEP arm against a background of 20% N. gonorrhoeae tetracycline resistance at the time of the trial.…”
Section: Antimicrobial Stewardship Resistance and Microbiota Impactsmentioning
confidence: 99%
“…However, STI co‐infection frequently occurs. For instance, multivariate analysis estimated that GBMSM with concurrent gonococcal or chlamydial infection had a 60% higher risk of syphilis compared with GBMSM without gonococcal or chlamydial infection 25 . Given the likelihood that gonococcal infections are frequently exposed to doxy‐PEP, this potentially undermines gonococcal antimicrobial stewardship efforts by accelerating the spread of gonococcal AMR 26 and potentially selecting for multidrug‐resistant gonococcal strains 27 .…”
Section: Antimicrobial Stewardship Resistance and Microbiota Impactsmentioning
confidence: 99%